Changes in Monosaccharide Content of Mucous Glycoproteins in Ulcerative Colitis. Issue 5867 (16th June 1973) - Teague, R. H.; Fraser, D.; Clamp, J. R.
Abstract : Colonic mucus appears to consist of two glycoprotein fractions, one of which contains mannose, whereas the other is mannose-free. The mannose-containing fraction is significantly increased in ulcerative colitis.